Stickiness in administrative approach of zakat institutions in Malaysia - Sarif, Suhaimi Mhd (IKAZ ACIS UITM, 2019)
Zakat institutions used administrative approach in managing the institutions to achieve social and economic objectiveness. Administrative approach has stickiness, which occurs in policy, practice and attitude. There are many factors contributing to stickiness. There can be related to human and non-human factors. Notably, human factors related to attitude and commitment. Thus it leads to inefficiency and ineffectiveness of the zakat institutions to alleviate poverty and bridge the gap between the rich and the poor. This will lead to inequality and no sustainable development socially as well as economically. This study interviewed zakat experts on the issues and challenges of stickiness in the administrative approach of zakat institutions. The results of the interview argued that administrative approach has been resulted from bureaucratic thinking, process and attitude.